Caracterização de poli(hexametileno biguanida) e suas blendas com poli(álcool vinílico) - Paula, Gustavo Figueira de (2012)
In this study, the physical-chemical characterization of poly(hexamethylene biguanide) hydrochloride, PHMB, was performed. It is a low molecular weight synthetic polymer with a broad-spectrum biocidal activity, widely used in aqueous formulations for industrial purposes. Dynamic Light Scattering, Thorque Reometry, Electrical Impedance Spectroscopy, Goniometry, UV/Vis Spectroscopy and Differential Scanning Calorimetry were used to probe the solvent-polymer interaction, determining that the properties presented by the material are strongly influenced by the nature of interactions between the hydroxyl groups of the solvent and the counter ion chloride from polymer. The polymeric nature of the material does not change the behavior of the biguanide group, whose properties remains unchanged compared to those of equivalent monomeric moiety, as evidenced by the formation of complexes with transition metals in nature very similar to biguanide and its derivatives. The polymer in solution behaves largely as a surfactant, and the tendency of micelle formation affects their film-forming properties. Blends with poly(vinyl alcohol) with high degree of hydrolysis (99%), PVOH, were studied by DSC, XRD, FTNIR, Thorque Rheometry and Electrical Conductivity; it showed miscibility in amorphous state, exhibiting regular solution behavior. The blends were semicrystalline up to 30% of mass fraction, composed by PVOH crystals with small inclusion of PHMB. The hypothesis that PVOH behaves as a solid solvent for PHMB was confirmed, which looks very useful for studying the properties of the latter aiming the development of new applications for this material. Electrospun mats of nanofibers were produced, and after further improvements, can be used as auxiliary treatment to heal wounds and external cirurgical interventions.